Production of recombinant human procollagen type I C-terminal propeptide and establishment of a sandwich ELISA for quantification - Seo, Woo-Young (Sci Rep, 2017)
Procollagen type I carboxy-terminal propeptide (PICP), derived from type I procollagen, has been identified as an indicator of type I collagen synthesis in bone matrix formation and skin recovery. PICP is a heterotrimeric glycoprotein consisting of two α1 chains (PICPα1) and one α2 chain (PICPα2). Here, we report the recombinant expression of human PICP using a mammalian expression system. Co-expression of PICPα1 and PICPα2 in HEK293F cells resulted in the production of functional PICP in the correctly assembled heterotrimeric form. Using the recombinant PICP as an antigen, we isolated PICP-specific human monoclonal antibodies from phage-displayed antibody libraries and raised rabbit polyclonal antibodies. Using those antibodies, we then developed a sandwich ELISA for PICP with a limit of detection of 1 ng/mL and a measurable range of 1–640 ng/mL. Both intra- and inter-assay imprecision values were <10%. For measuring PICP levels in human fibroblast cellular extracts and culture supernatants and a human serum, the developed ELISA kit displayed comparable performance to that of a commercialized kit. Our results provide an efficient production strategy for recombinant PICP, facilitating the generation of PICP-specific antibodies and development of PICP sandwich ELISA, with potential use in clinical diagnosis of serum samples and testing of cosmeceutical ingredients in fibroblast cell cultures.